2023
DOI: 10.3389/fcvm.2022.1046931
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics signature of epicardial adipose tissue for predicting postoperative atrial fibrillation after pulmonary endarterectomy

Abstract: PurposeThis study aimed to construct a radiomics signature of epicardial adipose tissue for predicting postoperative atrial fibrillation (POAF) after pulmonary endarterectomy (PEA) in patients with chronic thromboembolic pulmonary hypertension (CTEPH).MethodsWe reviewed the preoperative computed tomography pulmonary angiography images of CTEPH patients who underwent PEA at our institution between December 2016 and May 2022. Patients were divided into training/validation and testing cohorts by stratified random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, a similar response to statin administration was observed in normal-BMI and in overweight/obese patients. A variation in fat quality during statin therapy could in part explain statins' pleiotropic effects; in the future, advanced texture analyses [34] and radiomic-based applications [35,36] customized for EAT analysis could better investigate such effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, a similar response to statin administration was observed in normal-BMI and in overweight/obese patients. A variation in fat quality during statin therapy could in part explain statins' pleiotropic effects; in the future, advanced texture analyses [34] and radiomic-based applications [35,36] customized for EAT analysis could better investigate such effects.…”
Section: Discussionmentioning
confidence: 99%
“…The VOI image normalization and resampling were performed using the Pyradiomics package of Python Software (version 3.7, Python Software Foundation, DE, USA) as mentioned in our prior study [ 17 ]. In order to address the curse of dimensionality, which is particularly evident in high-dimensional data, we employed feature extraction techniques such as laplacian of gaussian (LoG) filters (sigma value of 1.0, 2.0, 3.0, 4.0, and 5.0) and wavelet transformation [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, recent studies have demonstrated a significant difference in the radiomics phenotype of EAT between patients with lone AF and the control group, and even between different AF subtypes 107,108 . Furthermore, some specific radiomics features, such as Gray‐Level Size Zone Matrix, can act as an independent predictor of AF recurrence, which might be of practical clinical value in AF management 108,109 …”
Section: The Association Of Eat With Cvd and Metabolic Disease: Clues...mentioning
confidence: 99%
“… 107 , 108 Furthermore, some specific radiomics features, such as Gray‐Level Size Zone Matrix, can act as an independent predictor of AF recurrence, which might be of practical clinical value in AF management. 108 , 109 …”
Section: The Association Of Eat With Cvd and Metabolic Disease: Clues...mentioning
confidence: 99%